Rare occurrence of bilaterally impacted mandibular supernumerary teeth - Vinay Kumar Bhardwaj; Jai Ram Kaundal; Anil Chug; Sanjeev Vaid; Abhishek Soni; Mohinder Chandel (Wolters Kluwer Medknow Publications, 2012)
Introduction: Supernumerary teeth are present in addition to the normal complement of teeth in permanent or deciduous dentitions. Incidence is high in permanent dentition, affects both the gender. They are more common in males, with the male to female ratio of 2:1. When the supernumerary teeth are causing problems such as, extensive resorption of adjacent teeth, hindering the eruption or malposition of permanent teeth, early surgical intervention is recommended. Case Report: A case of bilaterally impacted supernumerary premolars was reported when an orthopentomograph view was taken which revealed the presence of additional teeth impacted in relation to 35-36 and 45-46. Surgical removal was done as they were resorbing the roots of teeth in their vicinity. Discussion: Literature reports increased occurrence of the supernumeraries in the maxilla but supernumerary premolars are more likely to develop in the mandible. Etiology of supernumerary teeth is ambiguous and is due to following conditions:atavism or reversion, heredity, aberrations during embryologic formation, progress zone, and unified etiologic explanation.